International research management studies in interdisciplinary methods from business, government and academia - Birnbaum-More, Philip H.; Rossini, Frederick A.; Baldwin, Donald R. (Oxford University Press, 2011)
A group of papers describing the preconditions, processes, and outcomes of well-managed interdisciplinary research projects from the USA, Canada, Israel, Japan, Brazil, West Germany and Romania.